The Application of Computer-Mediated Communication in The RPL Program of The Bachelor and Master of Communication Sciences, Fajar University - Mariesa Giswandhani; Amalia Zul Hilmi (Eduvest - Journal of Universal Studies, 2025)
This study aims to determine the application of Computer-Mediated Communication in the Recognition of Past Learning (RPL) Program for Bachelor and Master of Communication Science at Fajar University. By using interpretive qualitative methods, the informants in this study were lecturers in undergraduate and master programs. The data collection techniques were carried out by in-depth interviews and also using snowball sampling techniques, non-participant observation and document studies. The results show that interactivity in online learning is highly dependent on effective communication between lecturers and students. Lecturers use quizzes and discussions to ensure the material is conveyed clearly, and encourage students to share relevant work experiences. Active participation in discussions, presentations and assignments gives students better grades, incentivizing engagement. Technologies such as Zoom and WhatsApp mediate communication, with Zoom for face-to-face lectures and WhatsApp for informal discussions. A Learning Management System (LMS) is also used to upload materials and schedules. Additional training for lecturers and technology support for students are necessary for successful online learning.